The Influence of Brand Promotion on The Reputation of Private Universities with Co-Creation as a Mediating Variable - Antika, Antika; Gunarto, Muji (International Journal of Business, Management and Economics, 2024)
This study evaluates the influence of private universities' brand promotion, co-creation, and reputation on the purchase intention of prospective students in Palembang. The variables studied include brand promotion as the independent variable, private university reputation as the dependent variable, and co-creation as the mediator variable. This study used quantitative analysis with hypothesis testing and involved eleven randomly selected alumni of private universities in Palembang. The results showed that brand promotion positively and significantly influences private university reputation and co-creation. In addition, co-creation also has a positive and significant influence on private college reputation and acts as a significant mediator in the relationship between brand promotion and college reputation. These findings confirm that brand promotion and co-creation play an essential role in enhancing the reputation of private colleges and attracting prospective students.